(untitled) (Bangladesh Journal of Medical Science, 2024)
Objective: Studies have recognized the numerous health benefits of Chrysophyllum albidum. This study examine the phytochemical evaluation of ethanolic leaf extract of C. albidum and its histological effects on the beta-cells of streptozotocin-induced diabetic rats. Method: Forty-two Sprague-Dawley rats (170- 200 g) were divided into six (n=7) groups. Groups 1 and 2 were given 10 mL of normal saline; group 3 was given 2 mg/kg of glibenclamide; and groups 4, 5, and 6 were given 125, 250, and 500 mg/kg/ day of C. albidum ethanolic leaf extract, respectively. Except for group 1, animals in groups 2-6 were injected intraperitoneally with 50 mg/kg streptozotocin after 14 days of oral treatment with normal saline, glibenclamide, and extract. For the next 14 days, rats were given normal saline, glibenclamide, and extract. The rats were fasted overnight before sacrifice on day 14; the pancreas was removed under diethyl ether anaesthesia and prepared for histological examination using a modified aldehyde fuchsin staining technique. Standard procedures were used for phytochemical evaluation and proximate analysis. Results: It was observed histological that the pancreatic tissues revealed cellular regeneration of the damage beta cells at a doses of 250 and 500 mg/kg/day. Phytochemical screening revealed the following; anthocyanin, cardiac glycosides, alkaloids, flavonoids, phenols, terpenoids, reducing sugar, and tannins while proximate analysis confirmed that the leaf contained 4.83% moisture, 39.59% crude fibre, 3.35% ash, 2.35% crude fats, 3.21% crude proteins and 46.71% carbohydrate. Conclusion: The results shows that C. albidum may possess a strong pharmacological activity owing to its rich phyto- constituents. This may have mediated its antidiabetic action by pancreatic beta cells regeneration. Hence, C. albidum could be a potential drug precursor for management of diabetes. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 63-73